CUSTOMER SATISFACTION TOWARDS KMRL – A STUDY - V.S, Athira; O, Chitra; P. , Balasubramanian (International Journal of Psychosocial Rehabilitation, 2020)
Whenever a business starts, the customers come ‘first’ , then only comes the profit, i.e., only when the customers are happy can a business earn profit. So, it is important for an organization to look into the needs and wants of the customer to survive and to succeed in the market. That’s how customer satisfaction became the key component for the success of any business. Therefore, the organization has to identify the factors that influence customer satisfaction and nurture them.